Copelatus Erichson from the Dominican Republic, with the description of a new species, comments on elytral striation and faunistic notes on Antillean species (Coleoptera: Dytiscidae: Copelatinae) - Manuel, Michaël; Deler-Hernández, Albert; Megna, Yoandri S.; Hájek, Jiří (Zootaxa, 2018)
The species of the genus Copelatus Erichson, 1832 occurring in the Dominican Republic are reviewed. Five species are recorded, with recent collecting data provided for four of them. Copelatus martini sp. nov., a member of the consors species group, is described and illustrated. It is compared to the apparently similar species C. guadelupensis Legros, 1948 based on morphological characters and on partial sequences of the CO1 gene. Interesting cases of intraspecific variability in the number of elytral dorsal striae in C. martini sp. nov. and C. vitraci are discussed in the light of the traditional taxo-nomic importance of this character for species group delimitation in Copelatus. Copelatus caelatipennis Aubé, 1838 and C. vitraci Legros, 1948 are recorded for the first time from the Dominican Republic (and therefore also from Hispaniola Island). The remaining species are C. posticatus (Fabricius, 1801), and C. insolitus Chevrolat, 1863 (for the latter, pre-sence in Hispaniola is doubtful and requires confirmation). Finally, C. guadelupensis is recorded from Puerto Rico for the first time, and a checklist of the Copelatus species of the Antilles is appended.